2007
DOI: 10.2106/jbjs.f.00497
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tourniquet Release in Knee Arthroplasty

Abstract: Therapeutic Level II. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 48 publications
0
45
1
3
Order By: Relevance
“…Consequently, they recommended that the tourniquet should be released after wound closure and that a compressive dressing should be applied [16] . Moreover, on the same subject, a meta-analysis of randomized controlled trials by Rama et al [17] in 2007, indicated that early tourniquet release for hemostasis increases blood loss, but also decreases the risk of regional postoperative complications (wound complications, symptomatic deep venous thrombosis and knee stiffness requiring manipulation) and the risk of reoperation. The first high-quality study that we noted in the last decade concerning the dilemma about the use of a tourniquet or not is the prospective randomized trial of Li et al [18] in 2009.…”
Section: Is It Necessary To Use a Tourniquet?mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they recommended that the tourniquet should be released after wound closure and that a compressive dressing should be applied [16] . Moreover, on the same subject, a meta-analysis of randomized controlled trials by Rama et al [17] in 2007, indicated that early tourniquet release for hemostasis increases blood loss, but also decreases the risk of regional postoperative complications (wound complications, symptomatic deep venous thrombosis and knee stiffness requiring manipulation) and the risk of reoperation. The first high-quality study that we noted in the last decade concerning the dilemma about the use of a tourniquet or not is the prospective randomized trial of Li et al [18] in 2009.…”
Section: Is It Necessary To Use a Tourniquet?mentioning
confidence: 99%
“…No advantage to using a tourniquet in knee replacement surgery for reduction of transfusion requirements Rama et al [17] Meta-analysis of randomized trials. Tourniquet release either before or after wound closure…”
Section: Tourniquet Use or Notmentioning
confidence: 99%
“…Major bleeding and blood transfusions after TKA occur in 3% to 5% [18] and 21% to 53% of patients [11,15,19], respectively. Various surgical techniques [9,11,16,17,19], medications [5,15,22], and postoperative protocols [2,4,8,12] to reduce bleeding have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Various surgical techniques [9,11,16,17,19], medications [5,15,22], and postoperative protocols [2,4,8,12] to reduce bleeding have been proposed. Various postoperative approaches including cold compresses [6], elastic bandage support [7], and compressive dressings [1] also have been reported for reduction of bleeding, soft tissue edema, and hemarthroses.…”
Section: Introductionmentioning
confidence: 99%
“…этому спо-собствуют очевидные преимущества, которые он позволяет получить: уменьшение продолжитель-ности оперативного вмешательства, снижение объема интраоперационной кровопотери, отлич-ная визуализация во время оперативного вмеша-тельства, обеспечение оптимальных условий для цементной фиксации имплантата [7][8][9].…”
unclassified